2017
DOI: 10.1002/pssr.201700052
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial pressure induced compensated half metal in Cr‐substituted iron(II) fluoride

Abstract: To design a compensated half metal (CHM), the substitution of Fe by Cr in the insulating antiferromagnetic FeF 2 compound is simulated by using first-principles calculations. The resultant compound Fe 0.5 Cr 0.5 F 2 crystallizes in orthorhombic Cmmm (No. 65) symmetry À and the AFM state (with antiparallel spins of Cr 2þ and Fe 2þ ) is favored. However, to realize half metallic character, uniaxial pressure (2.02 GPa along z axis) is critical. The magnetic ordering temperature calculated from mean field theory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our calculations indicated that for the selected U values, the main conclusions are consistent. Therefore, we choose the results from U Cr = 5.0 eV for discussion which is a typical value for 3d electrons . The results from other U values are provided in the supporting(Table S1 and Figure S1 and S2).…”
Section: Structure Parameters For Bulk (C2/m and R‐3) And Crcl3 Monolmentioning
confidence: 91%
See 2 more Smart Citations
“…Our calculations indicated that for the selected U values, the main conclusions are consistent. Therefore, we choose the results from U Cr = 5.0 eV for discussion which is a typical value for 3d electrons . The results from other U values are provided in the supporting(Table S1 and Figure S1 and S2).…”
Section: Structure Parameters For Bulk (C2/m and R‐3) And Crcl3 Monolmentioning
confidence: 91%
“…To achieve half metallic quantum state, a point defect with Cr vacancy is simulated. In fact, an insulator(semiconductor) to HM transition by band engineering is a new route to realize 100% spin polarization . To this end, several methods have been carried out.…”
Section: Structure Parameters For Bulk (C2/m and R‐3) And Crcl3 Monolmentioning
confidence: 99%
See 1 more Smart Citation